Peran Hamba Tuhan Dalam Memberitakan Injil Yang Murni Berdasarkan 1 Timotius 4:11-16 - Nahor Banfatin; Brayen Febrian Korompis; Djohan Rusli (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
A servant of God is identical with preaching the Gospel. From 1 Timothy 4:11-16 focuses on the actual roles of a God’s servant namelyexperiencing, enjoying and preaching the Gospel. The pure preachingdoes not only from one-sided life; which is the preaching itself, but also the wholeness of life which comprises enjoying and experiencing the Gospel; after that all of this can be applied through the preaching. This article uses a qualitative approach based on exegesis techniques and literature study. The source of this research focuses on the processing data from existing reference sources, both main and supporting sources, books and academic journals. There are some principles must applied based on the result of exegesis texts, namely command to preach the Gospel, living examples, perseverance in practicing gifts and self-control.